On The Formation of the Pedagogical Culture of Future Mathematics Teachers in the Context of the Implementation of the Competence- Based Approach - Sadykova, Elena Rashidovna (2021)
The relevance of the problem under study is due to the need to modernize the professional training of future teachers in the context of the implementation of the competence approach. One of the most effective methods for improving the training of a modern teacher is his subject and methodological training. In modern times, competitive teachers are in demand, possessing the necessary and sufficient types of professional activity, a high level of pedagogical culture. In the process of studying the formation of pedagogical culture, there was an elected teacher of mathematics. In the focus of the problems of the formation of the pedagogical culture of the future teacher, the problems of the formation of the pedagogical culture in the context of the implementation of the competence approach, associated with the specificity of the formation of the pedagogical culture of the teacher of mathematics, remain insufficiently studied. The article shows the content of the structural components of the teacher's pedagogical culture, developed and implemented the conditions for the formation of the pedagogical culture of the future mathematics teacher in the context of the competence approach. The leading research technologies are metacognitive technologies of a reflexive character with the means of information and communication technologies. The following methods were used in the study: theoretical (analysis of philosophical, psychological and pedagogical literature on the problem of research, study of mass and generalization of advanced pedagogical experience, pedagogical modeling), empirical (pedagogical observation, conversation, questionnaire, interviewing, testing). The materials of the article can be useful to future mathematics teachers, graduate students, teachers of higher educational institutions interested in the formation of teacher's pedagogical culture, and professional training of subject specialists.